Application of Cooperative Learning Models of Think Pair Shere Type to Improve Student Mathematics Learning Outcomes - Saputra, Andri; Zulkarnain, Zulkarnain; Saragih, Sehatta (Journal of Educational Sciences, 2019)
The low mathematics learning outcomes can be an indicator of student difficulty in learning mathematics. This study aims to analyze the influence of the application of the cooperative learning model Think Pair Share (TPS) type to the results of mathematics learning. This research used quasi-experimental research with sampling using stratified techniques and random sampling. The population was seventh grade students at SMP 17 Pekanbaru, SMP 12Pekanbaru, dan SMP 36 Pekanbaru. The instrument of this research was a daily test on the quadrilateral and triangle material to see student learning outcomes before being given treatment and after being given treatment. Statistical analysis was performed by Normality, Homogeneity Test, Independent Sample t-test, One Path Anova test, Two Path Anova Test. From the results of the collation test results obtained that p = 0.4425 and p = 0.4005, Ho is accepted, so there is no difference between the experimental class and the control class as well as the high school there is no difference, but the students' mathematics learning outcomes are reviewed from the level there are differences in the middle and lower schools. Generally, TPS learning is good at medium and low schools because in the learning process students still want to share knowledge with other students.